Supranational, National and Local Dimensions of Voter Turnout in European Parliament Elections. (27th February 2019) - Fiorino, Nadia; Pontarollo, Nicola; Ricciuti, Roberto
Abstract: We argue that the decision to vote in European Parliament (EP) elections is made at the intersection of three political dimensions: one related to the attitude of citizens towards the European Union (EU), one to the characteristics of the national political system and one associated with socioeconomic variables observed by voters at the local level. This article investigates this intersection by analysing the last four EP elections in the EU‐14, for 164 regions. We tested a multilevel model. The results indicate that compulsory voting, domestic political cleavages, labour market conditions and trust in the EU play a significant role. No evidence was found that GDP per capita affects turnout. Finally, the oldest segment of population seems more likely to vote than the youngest.